PATENTING OF MICROORGANISMS IN DEVELOPING COUNTRIES: THE INDIAN PERSPECTIVE - VINAY M S; GEETHA K N; NAGARAJA Y P (International Journal of Pharma and Bio Sciences, 2014)
Advances in biotechnology have made the patenting of microorganisms a subject of increased interest and controversy. This article deals with the major challenges faced by developing countries in understanding intellectual property rights (IPR) laws in the context of recent innovations in biotechnology involving microorganisms. The analysis of the data from Patent Facilitating Cell (DST, Govt of India) revealed the trends in various countries on the issue of patenting microorganisms which may help us to frame the system of patenting microbes. Indian machinery of patenting has to be geared up and also tuned to cope up with the new trend of patenting microorganisms. The strategies and policies to be adopted at present are also highlighted.